2011
DOI: 10.1182/blood-2010-08-302679
|View full text |Cite
|
Sign up to set email alerts
|

Results of allogeneic hematopoietic stem cell transplantation for chronic myelogenous leukemia patients who failed tyrosine kinase inhibitors after developing BCR-ABL1 kinase domain mutations

Abstract: Hematopoietic stem cell transplantation (HSCT) is effective therapy for patients with chronic myelogenous leukemia (CML) but is now mostly indicated for patients who develop resistance to tyrosine kinase inhibitors (TKIs), which can be associated with point mutations in BCR-ABL1. We reviewed the outcomes of imatinib-resistant CML patients (chronic phase, n ‫؍‬ 34; accelerated phase [AP], n ‫؍‬ 9; and blast phase [BP], n ‫؍‬ 4) who underwent HSCT and had BCR-ABL1 sequencing. Mutations were found in 19 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 40 publications
(54 reference statements)
3
38
0
1
Order By: Relevance
“…However, alloSCT remains an important therapeutic option for CML-CP in the following situations: patients who fail at least 2 TKIs and potentially patients harboring the T315I mutation after a trial of ponatinib therapy [70].…”
Section: Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, alloSCT remains an important therapeutic option for CML-CP in the following situations: patients who fail at least 2 TKIs and potentially patients harboring the T315I mutation after a trial of ponatinib therapy [70].…”
Section: Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
“…At present, alloSCT is the only curative therapy for accelerated and BP CML: overall cure rates are in the range of 15-40% and 5-20%, respectively [37,70]. Patients with cytogenetic clonal evolution as the only AP criterion have a long-term event-free survival rate of about 60% [84].…”
Section: Advanced Stage CMLmentioning
confidence: 99%
“…15 Allogeneic transplantation has been shown to be of benefit in patients who harbor BCR-ABL1 KD mutations, including the T315I mutation. 14,16 A retrospective analysis of patients transplanted with this mutation compared with a historical cohort showed that these patients appear to fare better with 2-year OS rates for chronic phase, accelerated phase, blast phase and Ph + ALL of 59%, 67%, 30% and 25%, respectively. 16,17 Only a few studies have analyzed transplant outcomes of patients who transformed to accelerated or blast phase.…”
Section: Introductionmentioning
confidence: 99%
“…12 In the original IRIS study, secondary resistance was deemed to occur at a rate of 4% annually, and was associated usually with a mutation in the BCR-ABL1 kinase domain. 6,13,14 Second-and third-generation TKIs have shown responses in patients with resistant mutations. 14,15 Recently, ponatinib has been approved for patients with T315I mutation based on a phase II study, which showed a 57% major cytogenetic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation